Moss-derived human complement factor H modulates retinal immune response and attenuates retinal degeneration - Mandy Hector; Verena Behnke; Paulina Dabrowska-Schlepp; Andreas Busch; Andreas Schaaf; Thomas Langmann; Anne Wolf (Journal of Neuroinflammation)
Abstract Background AMD is a multifactorial progressive disease of the central retina that leads to severe vision loss among the elderly. Genome-wide association studies in AMD patients and preclinical data have identified a dysregulated complement system and aberrant microglia responses in the pathogenesis of AMD. Specifically, a genetic variant in the complement factor H (CFH) gene, an important inhibitor of the alternative complement pathway, confers the strongest risk for AMD. Here, we investigated whether moss-derived recombinant human CFH proteins, termed CPV-101 and CPV-104, can modulate microglia reactivity and limit retinal degeneration in a murine light damage paradigm mimicking important features of AMD. Methods Two glycosylated human recombinant CFH proteins CPV101, and CPV-104 were produced in moss suspension cultures. In addition, glycans of the CPV-104 variant are sialylated, an optimization that makes CPV-104 an analog of human CFH. BALB/cJ mice received intravitreal injections of 5 µg CPV-101 and CPV-104 or vehicle, starting 1 day prior to exposure to 10,000 lx white light for 30 min. The effects of CPV-101 and CPV-104 treatment on mononuclear phagocyte and Müller cell reactivity were analyzed by immunostainings of retinal sections and flat mounts. Gene expression of microglia markers was analyzed using quantitative real-time PCR (qRT-PCR). Optical coherence tomography (OCT); Blue Peak Autofluorescence (BAF); terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining, and morphometric analyses were used to quantify the extent of retinal degeneration and photoreceptor apoptosis. Results Light-exposed mice treated with moss-derived recombinant human full-length CFH showed reduced complement activation and MAC deposition in the retina. Concomitantly, mononuclear phagocyte and Müller cell reactivity in light-exposed retinas were also ameliorated upon CFH substitution. Moreover, attenuated light-induced retinal degeneration was detected in mice that received moss-derived CFH. Conclusion Modulating the alternative complement pathway using moss-derived recombinant human full-length CFH variant CPV-101 and CPV-104 counter-regulate gliosis and attenuates light-induced retinal degeneration, highlighting a promising concept for the treatment of AMD patients.